Classification into a Novel Mollu-Series of Neutral Glycosphingolipids from the Lamp Shell, Lingula unguis - Kazuhiro AOKI; Sumiko SUGlYAMA; John T. DULANEY; Saki ITONORI; Mutsumi SUGITA (Journal of Oleo Science, 2002)
Seven neutral glycosphingolipids were isolated and purified from the lamp shell, Lingula unguis by successive column chromatography on ion exchange Sephadex (QAE-Sephadex), magnesium silicate (Florisil) and silicic acid (Iatrobeads). Their chemical structures were characterized as Glcβ1-1ceramide (CMS1, CMS2 and CMS3), Manβ1-4Glcβ1-1ceramide (MlOse2Cer, CDS), Manα1-3Manβ1-4Glcβ1-1ceramide (MlOse3Cer, CTS), GlcNAcβ1-2Manα1-3Manβ1-4Glcβ1-1ceramide (MlOse4Cer, CQS) and GlcNAcβ1-4GlcNAcβ1-2Manα1-3Manβ1-4Glcβ1-1ceramide (IV4βGlcNAc-MlOse4Cer, CPS) by compositional analysis, methylation analysis, exoglycosidase cleavage, gas-liquid chromatography, gas chromatograph-mass spectrometry and matrix-assisted laser desorption ionization time-of-flight mass spectrometry. Aliphatic constituents of CDS, CTS, CQS and CPS were virtually the same, with C16:0 and C18:0, and their 2-hydroxy homologues as the fatty acids, and octadecasphinga-4,8,10-trienine as the sole sphingoid. However, the ceramide compositions of CMS1, CMS2 and CMS3 differed from those of the other four glycolipids. The fatty acid composition of CMS1 consisted completely of C16:0, C17:0 and C18:0 acids, but both CMS2 and CMS3 contained instead of their 2-hydroxy homologues. The sphingoid components of CMS1 and CMS2 were octadecasphinga-4-enine and octadecasphinga-4,8,10-trienine, but that of CMS3 was entirely trihydroxysphingoid, 4-hydroxyoctadecasphiganine.